THE INFLUENCE OF FINANCIAL MANAGEMENT AND FINANCIAL LITERACY ON CO-OPERATIVE PERFORMANCE IN MALAYSIA - Siti Maslina Hamzah; Mohd Nor Hakimin Yusoff (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Co-operative firms in Malaysia play a vital role in national economic development, yet they continue to face ongoing challenges, particularly in the area of financial management. This study explores the link between financial management, financial literacy, and the performance of co-operatives in Malaysia. Based on existing literature, it is evident that sound financial management practices are positively correlated with improved co-operative performance. Previous research reveals that many co-operative shareholders lack adequate knowledge of financial management, which contributes to less-than-optimal performance. To bridge this gap, the study introduces a conceptual model that positions financial literacy as a moderating factor in the relationship between financial management and co-operative performance an element that has been largely neglected in earlier research. The findings underscore the need to enhance both financial management skills and financial literacy among co-operative stakeholders. The study recommends collaborative initiatives involving government bodies and non-governmental organizations to strengthen shareholders’ financial capabilities. Improving financial literacy is expected to not only lead to better individual financial decisions but also significantly enhance co-operative performance. Future studies should empirically test the proposed model and consider other influencing factors such as the size, age, and industry of the co-operative. Strengthening financial practices and literacy can pave the way for sustainable growth and enable co-operatives to make a greater contribution to Malaysia’s economic progress.